"Going boldly" in RE: fellowships strengthening teaching in challenging times in England - Orchard, Janet (Journal of Religious Education, 2025)
In this paper, we highlight the transformative potential of a sustained, subject-specific professional development model for religious education (RE) teachers' "pedagogical and subject knowledge" in the form of a Teacher Fellowship, based on key aspects of an earlier model offered by the Historical Association, and grounded in academic theology, dialogical pedagogy and collaborative inquiry. Through a pilot study, we demonstrate its potential to enhance teachers' subject confidence, promote deeper curricular reflection, and generate a renewed sense of professional purpose. While limited in scale, the findings support a replicable and scalable solution which addresses critical challenges in RE - particularly the growing reliance on non-specialist teachers and the subject's marginalisation in national educational priorities.